KINERJA KEUANGAN PERBANKAN TERHADAP PERTUMBUHAN LABA BANK SEBELUM DAN SELAMA PANDEMI COVID-19 - Wahyuni, Darlisma Dwi; Lautania, Maya Febrianty; Dinaroe, Dinaroe (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to analyze the effect of liquidity, solvency, and profitability on bank profit growth before and during the COVID-19 pandemic on banking companies listed on the Indonesia Stock Exchange in 20182021. This study uses secondary data with a purposive sampling technique in the IDX database and related banking, and the sample in this study is 19 banking companies listed on the IDX. From the research results, it was found that the loan-to-ratio, current ratio, debt-to-asset ratio, debt-to-equity ratio, net profit margin, and return on equity had a simultaneous effect on profit growth before and during the COVID-19 pandemic in banking companies. However, in terms of the COVID-19 effect on each variable, it has been found that there is no significant difference for each variable before and during COVID-19. It is believed this can happen because of the government's readiness through stimulus programs and the provision of low-interest rates, which greatly assist the banking industry. Furthermore, the banking policy of tightening credit during the COVID-19 period also helps banks to withstand the effects of COVID-19.